DAMPAK FATHERLESS TERHADAP PERKEMBANGAN PADA REMAJA - Tiara Tri Ananda Putri; R. Dhea Pratiwi Novrianti; Elfi Yulfienti; Maryeti Marwazi; Annisa Lidra Maribeth (Nusantara Hasana Journal, 2025)
The family is considered a fundamental institution that plays an important role in the formation of individuals, especially during the challenging teenage years. When one of the parents is not present, there is an imbalance in psychological development. Fatherless becomes interesting in relation to the unequal parenting of parents. Where the absence of a father in a teenager's life can be caused by the death or divorce of parents, resulting in children not being able to feel the love or presence of a father and experiencing emotional, intellectual and social problems in their lives. This research aims to determine the effect of fatherlessness on the self-control of adolescents who have lost the role of fathers both psychologically and socially. The method used in this research is a literature review.